MAHKOTA DEWA (PHALERIA MACROCARPA) SEBAGAI ANTINEFROTOKSISITAS âDEWA PENYELAMATâ DALAM PENURUNAN EFEK SAMPING CISPLATIN - Zulharini S, Meirizky; L.R, Annishfia; Hidayah, Siti Nurul; Iman, Naisbitt (Program Kreativitas Mahasiswa - Penelitian, 2013)
Cisplatin is one of the most widely used chemotherapeutic agent in cancer treatment, however it possess series of harmful adverse effects, most notably, nephrotoxicity. Due to that reason, a natural chemopreventive agent is needed to minimize cisplatinâs toxicity, namely, Mahkota Dewa fruit (Phaleria marcocarpa) extract. This research aim to determine anti nephrotoxic effect of mahkota dewa fruit on Vero cells, model of renal cells. Cytotoxic assay of mahkota dewaâs extract and cisplatin both single and combination was determined using MTT assay on HeLa cells and Vero cells. The cytotoxic assay resulted that IC50 value of cisplatin and Mahkota Dewa to HeLa cells were 18ÂµM (5,4 Âµg/mL) and 845 Âµg/mL, respectively, whereas the IC50 value of cisplatin and Mahkota Dewa to Vero were 80 ÂµM (24 Âµg/mL) and 730 Âµg/mL, respectively. The results indicated that cisplatin was more cytotoxic to HeLa cell in comparison to Vero cell. Combination treatment of mahkota dewaâs extract at 183 Âµg/mL and cisplatin 284 ÂµM showed increased viability of Vero cells. Therefore, combination treatment of cisplatin and mahkota dewa are able to decrease nephrotoxicity of cisplatin to renal cells.Â Â Keyword: Mahkota dewa, cisplatin, flavonoid, nephrotoxicity, HeLa cell, Vero cell